Particle image velocimetry measurements of induced separation at the leading edge of a plate - Stevenson, J; Nolan, K; Walsh, E (Cambridge University Press, 2016)
The free shear layer that separates from the leading edge of a round-nosed plate has been studied under conditions of low (background) and elevated (grid-generated) free stream turbulence (FST) using high-fidelity particle image velocimetry. Transition occurs after separation in each case, followed by reattachment to the flat surface of the plate downstream. A bubble of reverse flow is thereby formed. First, we find that, under elevated (7 %) FST, the time-mean bubble is almost threefold shorter due to an accelerated transition of the shear layer. Quadrant analysis of the Reynolds stresses reveals the presence of slender, highly coherent fluctuations amid the laminar part of the shear layer that are reminiscent of the boundary-layer streaks seen in bypass transition. Instability and the roll-up of vortices then follow near the crest of the shear layer. These vortices are also present under low FST and in both cases are found to make significant contributions to the production of Reynolds stress over the rear of the bubble. But their role in reattachment, whilst important, is not yet fully clear. Instantaneous flow fields from the low-FST case reveal that the bubble of reverse flow often breaks up into two or more parts, thereby complicating the overall reattachment process. We therefore suggest that the downstream end of the ‘separation isoline’ (the locus of zero absolute streamwise velocity that extends unbroken from the leading edge) be used to define the instantaneous reattachment point. A histogram of this point is found to be bimodal: the upstream peak coincides with the location of roll-up, whereas the downstream mode may suggest a ‘flapping’ motion.